2021
DOI: 10.31234/osf.io/ynbmr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Push Outcomes Bias Perceptions of Scratch Card Games

Abstract: In the domain of scratch card gambling, “pushes” refer to outcomes in which a prize is won that is equal to the cost of a scratch card game. Despite resulting in no net monetary gain, these outcomes are categorized as wins by lottery operators, effectively inflating published scratch card information (e.g., posted odds of winning). Additionally, the experience of obtaining a push shares similarities (e.g., the revealing of matching symbols) with the experience of obtaining a win and thus may be experienced sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…People who are more analytic also have better academic (Stanovich & West, 1998; and job performance (Alaybek et al, 2021;Corgnet et al, 2015;Otero et al, 2021). People who are more analytic also tend to have better financial performance (Corgnet et al, 2015) and fewer gambling problems (MacLaren et al, 2012;Walker et al, 2022). Analytic thinking is also associated with increased resistance to things like email fraud (Jones et al, 2019), online scams (Mosleh et al, 2021), and social media bots (Kenny et al, 2022).…”
Section: Evaluating the Evidence: Does Reason Matter?mentioning
confidence: 99%
“…People who are more analytic also have better academic (Stanovich & West, 1998; and job performance (Alaybek et al, 2021;Corgnet et al, 2015;Otero et al, 2021). People who are more analytic also tend to have better financial performance (Corgnet et al, 2015) and fewer gambling problems (MacLaren et al, 2012;Walker et al, 2022). Analytic thinking is also associated with increased resistance to things like email fraud (Jones et al, 2019), online scams (Mosleh et al, 2021), and social media bots (Kenny et al, 2022).…”
Section: Evaluating the Evidence: Does Reason Matter?mentioning
confidence: 99%
“…Theoretically, it has been argued that icon arrays are beneficial because they communicate in terms of relative frequencies rather than single-event probabilities (Tubau et al, 2019), they explicitly present information about how often the negative outcome is expected to occur and not to occur , they are more easily and automatically processed (Ancker et al, 2006;Trevena et al, 2013), and they result in deeper and more meaningful gist represenetations as opposed to surface-level verbatim representations (Brust-Renck et al, 2013). Empirically, icon arrays have been shown to help people solve Bayesian inference problems (Böcherer-Linder & Eichler, 2019;Brase, 2014;Tubau et al, 2019), improve their comprehension of relative and absolute risk-reduction statistics (Galesic et al, 2009;, reduce their susceptibility to gain-loss framing effects , and change their beliefs, emotions, and behavioral intentions in potentially adaptive ways (e.g., Nguyen et al, 2019;Walker et al, 2020). It is important to note, however, that not all studies have shown advantages of icon arrays over numerical representations (Etnel et al, 2020;Ruiz et al, 2013;Wright et al, 2009).…”
Section: Introductionmentioning
confidence: 99%